2002
DOI: 10.1207/s15327914nc431_6
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linoleic Acid Isomers and Mammary Cancer Prevention

Abstract: There is increasing evidence that individual isomers of conjugated linoleic acid (CLA) may have unique biological or biochemical effects. A primary objective of this study was to determine whether there might be differences in the anticancer activity of 9,11-CLA and 10,12-CLA. This was achieved by evaluating the reduction in premalignant lesions and carcinomas in the mammary gland of rats that had been treated with a single dose of methylnitrosourea and given 0.5% of either highly purified CLA isomer in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(61 citation statements)
references
References 49 publications
3
53
0
4
Order By: Relevance
“…It and the predominant natural isomer c9,t11-CLA, have been studied most extensively since they are each available commercially at relatively high purity. Although both CLA isomers were found to be equally efficacious in inhibiting rat mammary carcinogenesis [31] and angiogenesis [32], t10,c12-CLA is the more potent isomer in most in vitro studies. In TM4t mammary tumor cells, for example, we found that t10,c12-CLA is approximately five times more potent than c9,t11-CLA in decreasing viable cell number.…”
Section: Discussionmentioning
confidence: 96%
“…It and the predominant natural isomer c9,t11-CLA, have been studied most extensively since they are each available commercially at relatively high purity. Although both CLA isomers were found to be equally efficacious in inhibiting rat mammary carcinogenesis [31] and angiogenesis [32], t10,c12-CLA is the more potent isomer in most in vitro studies. In TM4t mammary tumor cells, for example, we found that t10,c12-CLA is approximately five times more potent than c9,t11-CLA in decreasing viable cell number.…”
Section: Discussionmentioning
confidence: 96%
“…Pariza et al (66) showed that both the cis-9, trans-11 and trans-10, cis-12 CLA isomers appear to be active in inhibiting carcinogenesis in animal models. Ip et al (70) showed that the anticancer effi cacies of the two isomers (cis-9, trans-11 CLA and trans-10, cis-12 CLA) were very similar. With the administration of both CLA, 6 weeks aft er carcinogen administration in rats, the total number of premalignant lesions was reduced by 33-36 %; at 24 weeks, the total number of mammary carcinomas was reduced by 35-40 %.…”
Section: Conjugated Linoleic Acidsmentioning
confidence: 99%
“…Adapted from Griinari and Bauman (1999). Ip et al, 2002;Kelley et al, 2007) and reduced adiposity (reviewed by Pariza, 2004), although only a mixed preparation including both cis-9, trans-11 and trans-10, cis 12 CLA was available in the original experiments. Similarly, this mixed CLA preparation also reduced milk fat yield in dairy cows (Loor and Herbein, 1998;Chouinard et al, 1999a and1999b).…”
Section: Biohydrogenation Intermediatesmentioning
confidence: 99%